Learning Information Ethical Decision Making With a Simulation Game - Lin, Weijane; Wang, Jui-Ying; Yueh, Hsiu-Ping (Frontiers in Psychology, 2022)
Taking advantage of the nature of games to deal with conflicting desires through contextual practices, this study illustrated the formal process of designing a situated serious game to facilitate learning of information ethics, a subject that heavily involves decision making, dilemmas, and conflicts between personal, institutional, and social desires. A simulation game with four mission scenarios covering critical issues of privacy, accuracy, property, and accessibility was developed as a situated, authentic and autonomous learning environment. The player-learners were 40 college students majoring in information science and computer science as pre-service informaticists. In this study, they played the game and their game experiences and decision-making processes were recorded and analyzed. The results suggested that the participants’ knowledge of information ethics was significantly improved after playing the serious game. From the qualitative analysis of their behavioral features, including paths, time spans, and access to different materials, the results supported that the game designed in this study was helpful in improving participants’ understanding, analysis, synthesis, and evaluation of information ethics issues, as well as their judgments. These findings have implications for developing curricula and instructions in information ethics education.